HF radiation pulse source locating in DIN-2K accelerator - Druj, O.S.; Yegorenkov, V.V.; Marchenko, S.V.; Yuferov, V.B. (Вопросы атомной науки и техники, 2022)
Experiments aimed at locating the source generating an HF pulse during the opening of the plasma switch and leading to explosive electron emission at the cathode were performed on DIN-2K pulse accelerator. It is demonstrated that certain lamps glow during the explosive electron emission pulse. This may point to the possible HF pulse generation during the opening of a plasma switch or radial interruption of current. In order to locate the radiation source the FR-2 dielectric insert was introduced into the vacuum diode and Ne lamps were placed over the anode mesh. The thickness of this insert was chosen to be larger than the electron penetration depth. The lack of Ne indicator lamps glow when the anode was shielded by an FR-2 insert was observed as opposed to the case of operation with the vacuum diode as a load. The virtual cathode caused by the explosive emission from the cathode is shown to be the source of HF radiation. На імпульсному прискорювачі ДІН-2К були проведені експерименти з метою визначення джерела генерації ВЧ-імпульсу при розмиканні плазмового ключа та генерації вибухової емісії електронів з катоду. Показано, що при екрануванні пучка електронів від аноду діелектричною вставкою з органічного скла, при чому довжина пробігу електронів у діелектрику менша за її товщину, на виході з вікна прискорювача не реєструвалися спалахи індикаторних неонових ламп, що постійно виникали при відсутності вставки. Для визначення джерела випромінювання була встановлена гетинаксова вставка, та індикаторні неонові лампи були розміщені на анодній сітці. Експерименти показали частковий спалах ламп при імпульсі вибухової емісії, що свідчить про можливе проходження ВЧ-імпульсу при розмиканні плазмової перетинки, або радіальному розмиканні струму. Показано, що джерелом випромінювання є віртуальний катод, що утворений вибуховою емісією катоду. На импульсном ускорителе ДИН-2К были проведены эксперименты с целью определения источника генерации ВЧ-импульса при размыкании плазменного ключа и генерации взрывной эмиссии электронов с катода. Показано, что при экранировании пучка электронов от анода диэлектрической оргстеклянной вставкой, причем длина пробега электронов в диэлектрике меньше ее толщины, на выходе из окна ускорителя не наблюдались вспышки индикаторных неоновых ламп, которые постоянно возникали при отсутствии вставки. Для определения источника излучения была поставлена гетинаксовая вставка, и индикаторные неоновые лампы были размещены на анодной сетке. Эксперименты показали частичное зажигание ламп при импульсе взрывной эмиссии, что свидетельствует о возможном прохождении ВЧ-импульса при размыкании плазменной перемычки, либо радиальном размыкании тока. Показано, что источником излучения является виртуальный катод, образованный взрывной эмиссией катода.